Application of chitosan-based flocculants to harvest microalgal biomass for biofuel production: A review. (July 2021) - Yin, Zhihong; Chu, Ruoyu; Zhu, Liandong; Li, Shuangxi; Mo, Fan; Hu, Dan; Liu, Chenchen
Abstract: An effective harvesting strategy with a low energy consumption as well as total cost is important for biofuel production. Microalgae harvesting by chitosan-based flocculants has received extensive attention, due to the outstanding structural features, biodegradability, applicability to various types of microalgae species and environmental friendliness. However, it is a significant strategy to select and prepare flocculants with high harvesting efficiencies for microalgae harvesting, based on different modifications strategies and external impact factors. This work reviews the latest research on chitosan-based flocculants for microalgae harvesting applications, including general aspects, harvesting mechanisms, several types of the dual harvesting system and surface modification methods commonly used to prepare chitosan-based flocculants. Suitable modification strategies for chitosan can achieve the high harvesting performance by improving synthetic effects and properties. The influences of external factors on microalgae harvesting are emphasized in detail. The effects of chitosan-based flocculants on downstream process are evaluated as well. This paper provides a potential prospect for future studies of chitosan-based flocculants on microalgae harvesting. Furthermore, uncertainties and research gaps of chitosan-based flocculants that exist in the usage of microalgae harvesting on a large scale have been put forward to foster the industry. Highlights: This paper reviews recent findings on microalgae harvesting using chitosan-based flocculants. Chitosan-based flocculants can be modified by dual harvesting system and surface modification. External factors affecting harvesting efficiency have been reviewed. More studies of chitosan-based flocculants are needed before engineering application on a large scale.